Demographic Oases in Shrinking Rural Areas: Exploring Trends in Galicia (Spain) and Northern Portugal - Alejandro Otero Varela; Inês Gusman; Carlos Alberto Patiño Romarís (Boletín de la Asociación de Geógrafos Españoles)
Despite their similar characteristics and shared challenges, Galicia and Northern Portugal are integrated into distinct national urban systems and have followed different territorial cohesion approaches. This study compares these regions to analyze their demographic dynamics and identify territories that exhibit resilience towards severe rural depopulation. Our findings reveal that both regions are intersected by the same Atlantic Urban Axis, where the highest population volumes and densities are concentrated. In contrast, the rural interior of the study area is experiencing strong and continuous demographic loss. However, upon examining demographic trends, alongside key socioeconomic indicators at a fine scale, we identify areas within predominantly rural regions that demonstrate resilience to decline. We termed them demographic oases. Our results indicate that the origins of these demographic oases are diverse —stemming from economic, administrative, and infrastructural factors— and, collectively, they play a crucial role in supporting their surrounding communities. Political approaches to territorial cohesion must acknowledge the significance of these oases, as their numbers are declining and they are essential for the sustainability of rural areas in both regions.